La révolution tunisienne : interactions entre militantisme de terrain et mobilisation des réseaux sociaux - Zeineb Touati (L’Année du Maghreb)
Without reducing the Tunisian revolution to a web 2.0 revolution or denying the role of social networks in the increasing mobilization of a large portion of Tunisian society, this article investigates the practical circumstances of the mobilization and use of social networks and ICT. We bring to light the changing role of social networks throughout the protests in Tunisia between December 17, 2010 (date of the first gatherings) and January 14, 2011 (date of Ben Ali’s departure) in response to the needs of on-the-ground mobilization and evolution of activists and protesters’ involvement. We specify the reasons and goals of the use of social networks and point out differences with the 2008 revolt in the mining area of Gafsa.